2019
DOI: 10.1111/jtxs.12450
|View full text |Cite
|
Sign up to set email alerts
|

How oral health and food sensory properties impact oral comfort during consumption of apples: A comparative approach in seniors and young adults

Abstract: Difficulties encountered during oral processing may cause food avoidance and increase the risk of malnutrition in older adults. The present survey aimed at comparing oral comfort experienced during consumption of apples in elderly and younger people. To do this, 122 participants divided into a senior group (65–83 years) and a control group (35–64 years) rated three varieties of apples (Gala, Granny Smith, Honey Crunch) using a “food comfortability” questionnaire related to general comfort, bolus formation, pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 64 publications
3
10
1
Order By: Relevance
“…This discrepancy may however rely on impaired participants’ sensory/motor abilities related to bolus formation and food ingestion, which have not presently been assessed. Statistical analysis demonstrated that the oral discomfort varied accordingly to the OHQoL and the occlusal status, which is consistent with previous reports 15,20 . The majority of participants experiencing oral discomfort complained about painless discomfort, lasting for few years, affecting the teeth and the gums surrounding teeth, induced by the contact between teeth or food products.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This discrepancy may however rely on impaired participants’ sensory/motor abilities related to bolus formation and food ingestion, which have not presently been assessed. Statistical analysis demonstrated that the oral discomfort varied accordingly to the OHQoL and the occlusal status, which is consistent with previous reports 15,20 . The majority of participants experiencing oral discomfort complained about painless discomfort, lasting for few years, affecting the teeth and the gums surrounding teeth, induced by the contact between teeth or food products.…”
Section: Discussionsupporting
confidence: 88%
“…Between December 2017 and January 2018, a sample of 125 subjects older than 35 years was invited to participate to the OralPom survey exploring food‐related oral comfort, food selectivity and oral conditions 20 . Living at home was considered as recruitment criteria.…”
Section: Methodsmentioning
confidence: 99%
“…This research was a part of a RENESSENS project, namely OralPom survey . The protocol received the approval of the Institut National de la Santé et de la Recherche Médicale (INSERM) Institutional Review Board (ID 17‐420) and the survey followed the ethical principles of the Helsinki Declaration and Good Clinical Practice.…”
Section: Methodsmentioning
confidence: 99%
“…Between December 2017 and January 2018, a sample of 125 subjects older than 35 years was invited to participate in the OralPom survey exploring food‐related oral comfort, food selectivity and oral conditions . Living at home was considered as recruitment criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation